Multiset controlled grammars: A normal form and closure properties - Ashaari, Salbiah; Turaev, Sherzod; Mohd Tamrin, Mohd Izzuddin; Okhunov, Abdurahim; Zhukabayeva, Tamara (Indonesian Journal of Electrical Engineering and Computer Science (IJEECS), 2017)
Multisets are very powerful and yet simple control mechanisms in regulated rewriting systems. In this paper, we review back the main results on the generative power of multiset controlled grammars introduced in recent research. It was proven that multiset controlled grammars are at least as powerful as additive valence grammars and at most as powerful as matrix grammars. In this paper, we mainly investigate the closure properties of multiset controlled grammars. We show that the family of languages generated by multiset controlled grammars is closed under operations union, concatenation, kleene-star, homomorphism and mirror image.